MKP1 Regulates the Induction of MUC5AC Mucin by Streptococcus pneumoniae Pneumolysin by Inhibiting the PAK4-JNK Signaling Pathway - Ha, Un-Hwan (American Society for Biochemistry and Molecular Biology, 2008)
Mucosal epithelial cells in the respiratory tract act as the first line of host innate defense against inhaled microbes by producing a range of molecules for clearance. In particular, epithelial mucins facilitate the mucociliary clearance by physically trapping the inhaled microbes. Up-regulation of mucin production thus represents an important host innate defense response against invading microbes. Excess mucin production, however, overwhelms the mucociliary clearance, resulting in defective mucosal defenses. Thus, tight regulation of mucin production is critical for maintaining an appropriate balance between beneficial and detrimental outcomes. Among various mechanisms, negative regulation plays an important role in tightly regulating mucin production. Here we show that the PAK4-JNK signaling pathway acted as a negative regulator for Streptococcus pneumoniae pneumolysin-induced MUC5AC mucin transcription. Moreover pneumolysin also selectively induced expression of MKP1 via a TLR4-dependent MyD88-TRAF6-ERK signaling pathway, which inhibited the PAK4-JNK signaling pathway, thereby leading to up-regulation of MUC5AC mucin production to maintain effective mucosal protection against S. pneumoniae infection. These studies provide novel insights into the molecular mechanisms underlying the tight regulation of mucin overproduction in the pathogenesis of airway infectious diseases and may lead to development of new therapeutic strategies.